Prevalence of Frailty and Associated Factors in a US‐Wide Cohort of Rheumatic Diseases - Katherine D. Wysham; Catherine L. A. Chang; Namrata Singh; James S. Andrews; Kristin Wipfler; Sarah B. Lieber; Sebastian E. Sattui; Rachael Stovall; Joshua F. Baker; Patricia P. Katz; Kaleb Michaud (ACR Open Rheumatology)
Objective We quantified the prevalence of self‐reported frailty and identified associated factors in a US‐wide cohort of people with rheumatic and musculoskeletal diseases (RMDs). Methods Frailty was measured using the FRAIL scale, a patient‐reported frailty instrument, in FORWARD, The US‐based National Databank for Rheumatic Diseases. Frailty prevalence was determined overall and by individual RMD, which included rheumatoid arthritis, connective tissue diseases (CTDs), osteoarthritis (OA), fibromyalgia, spondyloarthritis (SpA), and vasculitis. Multivariable logistic regression models evaluated the cross‐sectional associations between RMDs and frailty, as well as factors associated with frailty within each RMD. Results Among 4,345 individuals, 1,422 were frail (33%). Participants were on average 67.1 ± 11.6 years of age, 82% were female, and 89% self‐identified as White. Difficulty with ambulation was the most common frailty feature. With OA as referent, those with CTD had a higher odds of frailty (odds ratio [OR] 1.44, 95% confidence interval [CI] 1.01–2.04), and those with SpA had a lower odds (OR 0.45, 95% CI 0.31–0.67). Age, female sex, pain, disease severity, disease duration, and elevated body mass index categories were all associated with frailty. In the RMD‐stratified analyses, disease severity remained associated with frailty in all RMDs except vasculitis. Conclusion Frailty was present in 1 in 3 participants with RMDs, a higher prevalence than estimates from the general population, and primarily manifests as difficulty with mobility. Disease severity was consistently associated with an increased odds of frailty across RMDs. Future interventions to improve physical activity and prevent disease damage may improve frailty status in people with RMDs.